Evaluation of the Medicinal and Aromatic Plants Processing Sector in Hatay Province - Ahmet Duran Çelik; Aykut Gül (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the medicinal and aromatic plants sector of the Hatay province was evaluated with the SWOT Analysis (strengths, weaknesses, opportunities, and threats), and aimed to offer solutions for the development of the sector based on the opinions of the companies which are operating in the province. According to the research results, the rich natural vegetation of the province and its proximity to raw material resources, were found as the main 'strengths'. Insufficient incentives, lack of coordination, problems in accessing quality raw materials, and adulteration were found as the 'weaknesses'. Increase in demand and high added value potential, and the EXPO 2021 exhibition were found as the 'opportunities'. Security problems in the region due to the ongoing war in Syria were determined as the prominent 'threat'.